High throughput silencing identifies novel genes in endometrioid endometrial cancer - Md Fuzi, Afiqah Alyaa; Omar, Siti Zawiah; Mohamed, Zahurin; Noor Azmi, Mat Adenan; Mokhtar, Norfilza Mohd (Elsevier, 2018)
Objective: To validate the gene expression profile obtained from the previous microarray analysis and to further study the biological functions of these genes in endometrial cancer. From our previous study, we identified 621 differentially expressed genes in laser-captured microdissected endometrioid endometrial cancer as compared to normal endometrial cells. Among these genes, 146 were significantly up-regulated in endometrial cancer. Materials and Methods: A total of 20 genes were selected from the list of up-regulated genes for the validation assay. The qPCR confirmed that 19 out of the 20 genes were up-regulated in endometrial cancer compared with normal endometrium. RNA interference (RNAi) was used to knockdown the expression of the upregulated genes in ECC-1 and HEC-1A endometrial cancer cell lines and its effect on proliferation, migration and invasion were examined. Results: Knockdown of MIF, SOD2, HIF1A and SLC7A5 by RNAi significantly decreased the proliferation of ECC-1 cells (p < 0.05). Our results also showed that the knockdown of MIF, SOD2 and SLC7A5 by RNAi significantly decreased the proliferation and migration abilities of HEC-1A cells (p < 0.05). Moreover, the knockdown of SLC38A1 and HIF1A by RNAi resulted in a significant decrease in the proliferation of HEC1A cells (p < 0.05). Conclusion: We have identified the biological roles of SLC38A1, MIF, SOD2, HIF1A and SLC7A5 in endometrial cancer, which opens up the possibility of using the RNAi silencing approach to design therapeutic strategies for treatment of endometrial cancer.